2016
DOI: 10.1017/s0022149x16000092
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels and codon usage patterns in nuclear genes of the filarial nematodeWucheraria bancroftiand the blood flukeSchistosoma haematobium

Abstract: Synonymous codons are used with different frequencies, a phenomenon known as codon bias, which exists in many genomes and is mainly resolute by mutation and selection. To elucidate the genetic characteristics and evolutionary relationship of Wucheraria bancrofti and Schistosoma haematobium we examined the pattern of synonymous codon usage in nuclear genes of both the species. The mean overall GC contents of W. bancrofti and S. haematobium were 43.41 and 36.37%, respectively, which suggests that genes in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…as preponderant forces. More recently, studies on S. haematobium and S. japonicum confirmed a major role of natural selection in shaping the codon usage bias in these species (Mazumder et al, 2017a; Mazumder et al, 2017b). Several studies analyzed codon usage on the available genomes and transcriptomes of Taenidae species showing weak codon bias and a higher GC3 in highly expressed genes explained by combined mutational and selection forces (Chen et al, 2013; Yang et al, 2014; Yang et al, 2015; Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…as preponderant forces. More recently, studies on S. haematobium and S. japonicum confirmed a major role of natural selection in shaping the codon usage bias in these species (Mazumder et al, 2017a; Mazumder et al, 2017b). Several studies analyzed codon usage on the available genomes and transcriptomes of Taenidae species showing weak codon bias and a higher GC3 in highly expressed genes explained by combined mutational and selection forces (Chen et al, 2013; Yang et al, 2014; Yang et al, 2015; Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Besides the effect at synonymous codon usage, it has been shown that strong GC bias could lead to changes in amino acid frequencies (Behura and Severson, 2013; Li et al, 2015). While this has not been explored widely in flatworms, several advances have been made in nematodes (Cutter et al, 2006; Mitreva et al, 2006; Mazumder et al, 2017a; Mazumder et al, 2017b). It is not clear yet how genomic GC differences could be influencing the codon usage and amino acid composition of proteins in Platyhelminthes and if these variations correlate with the ecological and physiological diversity in the phylum.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the AT and GC skews in 30 avian mitochondrial genomes revealed that parrots have unusually strong compositional asymmetry (AT-and GC-skew) in their coding sequences (Eberhard and Wright, 2016). In W. bancrofti and S. haematobium, the GC, AT, purine, pyrimidine, amino, and keto skews were negatively associated with CUB, except for the pyrimidine skew in S. haematobium (Mazumder et al, 2017). Contrarily, in amphibians Bombina bombina, B. fortinuptialis, B. lichuanensis, B. maxima, B. microdeladigitora, B. orientalis, and B. variegate, no skew was correlated to CUB (Barbhuiya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation between the effective number of codons (ENC) and different skews (GC, AT, purine, pyrimidine, amino, and keto skews) has also been reported in Wuchereria bancrofti and Schistosoma haematobium , wherein all the skews were negative in both the organisms, except for that of pyrimidine in S. haematobium . This suggests a significant role of CUB on nucleotide disproportion ( Mazumder et al, 2017 ); however, the different skews represent a marker for a specific genus and species.…”
Section: Introductionmentioning
confidence: 98%